Solve -5*b = 3*m - 24, -11*m + 8*m + 21 = 4*b for b.
3
Solve 4 = -m + q, 2*q = 9 + 1 for m.
1
Solve 4*j = -3*q + 17, -39 = 3*j + q - 48 for j.
2
Solve -2*i + 0 + 14 = -4*h, -h - 3*i = -7 for h.
-2
Solve 0 = -2*m + 4*g + 18, -4*g = -6*g - 10 for m.
-1
Solve b = 4*c - 13, -11 = 2*c - 4*c + 5*b for c.
3
Solve -3*p + 2*i = 9 + 9, 0 = 3*p - 4*i + 24 for p.
-4
Solve -20 = -4*s, -3*s = 2*w - s for w.
-5
Solve 3*k - 6*i - 11 = -2*i, 4*i = -2*k - 6 for k.
1
Solve -3*j + 1 = -v, 0 = -v - 10*j + 14*j - 2 for v.
2